2024
DOI: 10.1292/jvms.23-0269
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles associated with early relapse during first remission induction in canine multicentric high-grade B-cell lymphoma

Hiroto TOYODA,
Akiyoshi TANI,
Yuko GOTO-KOSHINO
et al.

Abstract: Although chemotherapy using CHOP-based protocol induces remission in most cases of canine multicentric high-grade B-cell lymphoma (mhBCL), some cases develop early relapse during the first induction protocol. In this study, we examined the gene expression profiles of canine mhBCL before chemotherapy and investigated their associations with early relapse during the first whole CHOP-based protocol. Twenty-five cases of mhBCL treated with CHOP-based protocol as first induction chemotherapy were included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…RNA-Seq of canine mammary tumours ( n = 157) identified three gene expression-based subtypes, one of which was transcriptionally similar to basal-like human breast cancer [ 84 ]. More recently, the gene expression profiles of canine multicentric high-grade B-cell lymphoma ( n = 25) were assessed by RNA-Seq to compare cases where the subjects completed the chemotherapy protocol without relapse, versus those that relapsed during the treatment, and found that both changes in the tumour cells themselves and changes in the immune cell-tumour cell interactions were associated with chemotherapy efficacy [ 92 ]. Finally, other recent studies used RNA-Seq (adapted for small RNA sequencing) to analyse the differential expression of miRNAs in canine diffuse large B-cell lymphoma (6 samples) relative to controls (4 non-neoplastic samples) [ 93 ], and FFPE duodenal samples from canines with intestinal T-cell lymphoma ( n = 9) relative to those with inflammatory bowel disease ( n = 12) and to those with no/minimal inflammation [ 54 ].…”
Section: Methods For the Genetic Characterisation Of Tumour Cells In ...mentioning
confidence: 99%
“…RNA-Seq of canine mammary tumours ( n = 157) identified three gene expression-based subtypes, one of which was transcriptionally similar to basal-like human breast cancer [ 84 ]. More recently, the gene expression profiles of canine multicentric high-grade B-cell lymphoma ( n = 25) were assessed by RNA-Seq to compare cases where the subjects completed the chemotherapy protocol without relapse, versus those that relapsed during the treatment, and found that both changes in the tumour cells themselves and changes in the immune cell-tumour cell interactions were associated with chemotherapy efficacy [ 92 ]. Finally, other recent studies used RNA-Seq (adapted for small RNA sequencing) to analyse the differential expression of miRNAs in canine diffuse large B-cell lymphoma (6 samples) relative to controls (4 non-neoplastic samples) [ 93 ], and FFPE duodenal samples from canines with intestinal T-cell lymphoma ( n = 9) relative to those with inflammatory bowel disease ( n = 12) and to those with no/minimal inflammation [ 54 ].…”
Section: Methods For the Genetic Characterisation Of Tumour Cells In ...mentioning
confidence: 99%